FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PERUSAHAAN PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - JOHN WILLIAM; RIKI SANJAYA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2017)
The purpose of this study is to examine the factors that influence dividend policy in non financial companies also wheter managerial ownership could moderated effect total debt to firm performance. These factors are total debt, size, age, institutional ownership, liquidity, tangibility, asset turnover, growth.Population of this research are non financial companies listed Indonesia Stock Exchange from 2012-2015. The samples of this study are 330 using purposive sampling method. This research uses multiple regression method to test the hypothesis.The result of this study shows that managerial ownership is can moderated total debt. Total debt, size, and asset turnover have influence to firm performance but age, institutional ownership, liquidity, tangibility, and growth do not have influence to firm performance